Commercial grade dedication challenges for Brazilian nuclear industry (Brazilian Journal of Radiation Sciences (BJRS), 2021)
According to NRC, the commercial-grade dedication is a process by which a commercial-grade item (CGI) is designated for use as a basic component. This acceptance process is undertaken to provide reasonable assurance that a CGI to be used as a basic component will perform its intended safety function and, in this respect, is deemed equivalent to an item designed and manufactured under a quality assurance program. This assurance is achieved by identifying the critical characteristics of the item and verifying their acceptability by inspections, tests, or analyses by the purchaser or third-party dedicating entity. In Brazil there are two Nuclear Power Plants in operation, one is American design (Angra 1), other is German design (Angra 2) and one is under construction that is German design (Angra 3). The nuclear safety items are imported and many of them are obsolete and besides the process of purchasing imported items is very complicated. If the nuclear industry in Brazil adopt the Commercial-grade dedication it will improve the internal market and facilitate the process of purchasing items. The Brazilian Quality Assurance Standard (Cnen NN 1.16) shows the 18 Basic requirements of 10 CFR 50 App B, so the Brazilian Industry can be qualified according to this Brazilian standard. The critical characteristics identification and the testing process is an engineering responsibility that Brazilian engineer can perform. This work shows the challenge of commercial-grade dedication in Brazil and discuss the importance of this process to the operation of the nuclear power plants in Brazil, including the long-term operation and others Brazilian nuclear projects..